2007
DOI: 10.1152/ajpcell.00597.2006
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of Na+/K+-ATPase isoform distribution in rat ventricular myocytes

Abstract: Despa S, Bers DM. Functional analysis of Na ϩ /K ϩ -ATPase isoform distribution in rat ventricular myocytes. Am J Physiol Cell Physiol 293: C321-C327, 2007. First published March 28, 2007; doi:10.1152/ajpcell.00597.2006.-The Na ϩ /K ϩ -ATPase (NKA) is the main route for Na ϩ extrusion from cardiac myocytes. Different NKA ␣-subunit isoforms are present in the heart. NKA-␣1 is predominant, although there is a variable amount of NKA-␣2 in adult ventricular myocytes of most species. It has been proposed that NKA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
59
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 25 publications
8
59
1
1
Order By: Relevance
“…Therefore, GRX coordinates the activity of numerous redox-sensitive proteins adjusting to the changes in the redox microenvironment (Fig. 5, C and D) (35)(36)(37). Spontaneous deglutathionylation catalyzed by GRX and thioredoxins is most likely to be the cause of the gradual loss of the inhibitory effect of ischemia on the Na,K-ATPase in heart tissue homogenate with time, as reported by Fuller et al (12).…”
Section: S-glutathionylation Of ␣ Subunit Leads To Completementioning
confidence: 63%
See 1 more Smart Citation
“…Therefore, GRX coordinates the activity of numerous redox-sensitive proteins adjusting to the changes in the redox microenvironment (Fig. 5, C and D) (35)(36)(37). Spontaneous deglutathionylation catalyzed by GRX and thioredoxins is most likely to be the cause of the gradual loss of the inhibitory effect of ischemia on the Na,K-ATPase in heart tissue homogenate with time, as reported by Fuller et al (12).…”
Section: S-glutathionylation Of ␣ Subunit Leads To Completementioning
confidence: 63%
“…The ␣2 isoform of the catalytic subunit is mainly localized in the T-tubular zones, where it is associated with the Na ϩ /Ca 2ϩ exchanger (36). Thus, S-glutathionylation and the following inhibition of the ␣2␤ isozyme may have a profound effect on the intracellular Ca 2ϩ handling in cardiomyocytes (36,37,39). As the ␣2 isoform has been reported to be particularly prone to oxidation (8), more favorable binding of glutathione to this isoform will protect it from oxidation.…”
Section: S-glutathionylation Of ␣ Subunit Leads To Completementioning
confidence: 99%
“…We switched to the ouabain-containing superfusate 8 -10 min after the whole-cell configuration had been established in all experiments. As the effect of ouabain is not reversible within the time frame that stable holding currents can be reliably measured (22,23), the suspension of myocytes was removed at the conclusion of the experimental protocol, and a new aliquot of myocytes was added to the tissue bath in ouabain-free solution. As a consequence, only one myocyte was studied per bath.…”
Section: Methodsmentioning
confidence: 99%
“…However, things are less clear in the heart. The functional density of NKA-␣2 is significantly higher in the T-tubules (versus external sarcolemma) in cardiac myocytes from both rats (16,17) and mice (18), but their precise localization with respect to the junctions with the sarcoplasmic reticulum is not known. Based on Ca 2ϩ transients from heterozygous NKA-␣1 ϩ/Ϫ and NKA-␣2 ϩ/Ϫ mice, James et al (19) concluded that NKA-␣2 is involved in cardiac myocyte Ca 2ϩ regulation, whereas NKA-␣1 is not.…”
mentioning
confidence: 99%